Impact of some husbandry practices on productive and reproductive traits of desert goats (Capra hircus) in South Darfur State, Sudan - Abderahman, H.; Abu Nikhaila, A. M.; Abdurahman, A.; Ethahir, H. A. (Journal of the Indonesian Tropical Animal Agriculture, 2025)
This study evaluated the effects of husbandry practices on the productivity and reproduction of Sudan Desert goats. Conducted from 2014 to 2016 in South Darfur, it involved 40 female goats matched by body weight, age, physiological status, and parity. The interventions tested were shaded versus unshaded housing, restricted versus free suckling, and early versus traditional weaning. Datawere analyzed using SPSS with significance at P<0.05. Surveys revealed that goat farming provided both milk and financial security. Most owners relied on hay, with only 5% using concentrates. Under traditional management, milk yield averaged 75.88 kg over 98.5 days. Challenges included disease (notably pneumonia at 61.5%), limited capital (26.2%), and poor pasture (22.3%). Experimentally, un-shaded housing resulted in higher birth and weaning weights and better kid survival, especially with free suckling and delayed weaning. However, shaded housing shortened the kidding interval, improv-ing reproductive performance. SingleSingle-born and male kids also had higher birth weights. The study con-cludes that shaded housing enhances reproduction, while unshaded conditions with improved suckling and weaning boost kid growth and survival. Recommendations include better veterinary support, regu-lated drug use, improved pasture, and supplementary feeding to increase goat productivity in the re-gion.